Interference‐aware MAC scheduling and admission control for multiple mobile WBANs used in healthcare monitoring1. (6th March 2014) - Mahapatro, Judhistir; Misra, Sudip; Mahadevappa, Manjunatha; Islam, Nabiul
Summary In this paper, we address the problem of interference when multiple time division multiple access‐based wireless body area networks (WBANs) come in the proximity of one another. We propose a simple solution that creates common non‐conflicting schedule between these interfering WBANs. Our proposed scheme allows the reuse of maximum possible time slots among WBANs that are two‐hop neighbors of one another. A flow admission control scheme is applied to control the flows during the period of interference. We show that the percentage of flows admitted because of flow control decreases with the increase in the network size and flow rate. We simulated a scenario where WBANs move randomly within a simulation area with a certain speed and meet at a particular point. We show that the signal to interference noise ratio (SINR) value of WBANs changes as long as they are within the transmission range of one another. Also, we show that the exchanges of common schedule (which is dependent on the number of times the SINR value drops below the threshold) are required in order to improve the packet delivery ratio in WBANs. Copyright © 2014 John Wiley & Sons, Ltd.